Association of bone mineral density with a first-degree family history of diabetes in normoglycemic postmenopausal women. Issue 11 (November 2019) - Yang, Lijuan; Hu, Xiang; Zhang, Hailing; Pan, Wei; Yu, Weihui; Gu, Xuejiang
Abstract: Objective: A first-degree family history of diabetes (FHD) contributes to increased risks of metabolic and cardiovascular diseases. Bone is an insulin-resistant site and an organ susceptible to microvascular complications. The goal of the present study was to investigate the association of FHD with bone mineral density (BMD) in postmenopausal women. Methods: In all, 892 normoglycemic postmenopausal women were divided into subgroups of participants with or without a first-degree FHD. BMD was measured using dual-energy x-ray absorptiometry. Fasting plasma insulin and glucose levels were measured, and insulin resistance was evaluated using the Homeostasis Model Assessment—Insulin Resistance (HOMA-IR) index. Results: The BMD of the lumbar spine and femoral neck were much higher in the participants with a first-degree FHD than in those without an FHD (all P  < 0.05). Lumbar spine BMD and femoral neck BMD were both positively associated with HOMA-IR ( P  = 0.041 and P  = 0.005, respectively). Multiple stepwise regression analysis showed that a first-degree FHD was an independent factor that was positively associated with lumbar spine BMD (standardized β  = 0.111, P  = 0.001) and femoral neck BMD (standardized β  = 0.078, P  = 0.021). A first-degree FHD was associated with increased BMD, insulin resistance, and hyperinsulinemia. Conclusions: Our study indicated that normoglycemic postmenopausal women with a first-degree FHD exhibit increased BMD with insulin resistance and hyperinsulinemia. A first-degree FHD was an independent factor associated with elevated BMD in Chinese women after menopause.